A combined technique for rotor broken bar diagnosis in VSD equipped with vibration reducers. (1st January 2014) - Hanafy, Hanafy Hassan; Hussien, Ahmed M.; El-Zahab, Essam El-Din Abou
Broken rotor bar is a common fault in squirrel cage induction motors. Rotor failures due to that fault now account for a moderate percentage of total induction motor failures. This paper will deal with detection of broken rotor bar of induction motor supplied from variable speed drive (VSD) equipped with AC reactor and sine-wave shaping filter on the output side. The experimental results show that the instantaneous power spectrum analysis method is only effective when the motor is supplied from sinusoidal supply, in contrast for the demonstrated VSD. The instantaneous power spectrums of the healthy rotor case and the broken bar rotor cases is processed with mean absolute difference (MAD) approach algorithm to investigate the dissimilarity between them. The results show that this combined technique is highly effective in the diagnosis of broken rotor bar fault in case of the demonstrated VSD.